A DNA based method to determine the origin of honey produced by Apis cerana - Szepesi, Kinga; Heltai, Botond; Kolics, Éva; Mátyás, Kinga; Kálmán, Nikoletta; Taller, János; Miyazaki, Satoshi; Kolics, Balázs (GEORGIKON FOR AGRICULTURE, 2022)
The value of a product is derived from various components, such as its functionality, availability on the market, origin, raw material, exclusivity; in case of food products not least taste and health effects. In this approach honey has an outstanding position because of its reputation in the food and health industry. The honey of the Asian honey bee is unique and of great value, and because of this it is often prone to adulteration. Asian honey is restricted to those countries where the Asian honey bee is endemic. Beekeeping with this species of bee in these areas is part of cultural tradition. The idea of this work is to design a fast and accurate detection method for adulteration, in the interest of preserving the value of the honey produced by the Asian honey bee (Apis cerana). The purpose of the study was to point out the genetic differences between two close honey bee species (A. cerana and A. mellifera) and to use mitochondrial loci to develop a molecular method to confirm the entomological origin of honey deriving from a Cerana apiary. The markers designed besides being suitable per se can be adopted as a part of a genetic analysis panel.
Keywords: Apis cerana; ethnic honey; molecular marker; honey authenticity; adulteration